Mga Ati sang Tina a research on communication symbols of the Ati marriage and healing rituals in Antique supplemented with a video documentary - Abalajon, Inaj Mae Portugalete; Clores, Pauline Baysa; Fandinola, Ciara Robyn Fernandez (2016.)
Field studies in organizational communication include complex methods in data collection and analysis through interviews and production of video ethnography. This research focuses on the ethnography of the indigenous peoples (IPs), specifically the Atis. They hold the richest and most genuine culture the Philippines has. One important component that makes up culture is the rituals by the IPs that make up various symbols that bear meanings important to the communities where they belong to. However, through the years, these symbols are slowly fading because of the rise of the new technologies. The waning purity of the rituals, together with its communication symbols, influenced this research to use media in preserving its remaining nature before it dies out. Through a video documentary, a concrete material can be passed through generations. This material with combination of facts and visuals creates a consistent and more efficient way of preserving what lacks in oral tradition. The researchers chose the Ati community in Brgy. Tina, Hamtic, Antique as subjects of this research. They used descriptive analysis in conducting the study. The data was gathered through participatory observation, SWOT analysis, ocular visits and immersion. The study outlined its framework according to the Organizational Culture Theory. The theory states that communication symbols are present in a community through verbal, physical and behavioural symbols. Another theory used in the study is the theory of Semiotics. The meanings behind these symbols are what we called the signified, while the symbols or objects attached to these meanings are the signifiers. Interviews were conducted to identify directly the meanings of the communication symbols from the Atis and experts themselves. The researchers were able to gather communication symbols (signifiers) from the marriage and healing rituals of the Ati community. Significantly, the meanings (signified) of these symbols show the Ati community?s strong feudal ties, and high respect for spirits and unseen forces. Furthermore, the lifestyle of the community depends on the available resources in their environment.
Thesis (Undergraduate, Bachelor of Arts in Communication and Media Studies) University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Indigenous people; Culture -- Ati -- Antique; Rituals -- Ati; Video documentary; Organizational culture theory; Communication symbols